Pengaruh Penerapan Kurikulum Merdeka Belajar Terhadap Hasil Belajar Peserta didik Pada Mata Pelajaran Fiqih di MTs Negeri 2 Bandar Lampung - Selvia, Devi Sela Eka; Pahrudin, Agus; Suri, Indah Resti Ayuni; Betria, Arjuni (Universitas PGRI Semarang, 2024)
This study aims to determine the effect of the implementation of the independent learning curriculum on student learning outcomes in the Fiqh subject at MTs Negeri 2 Bandar Lampung. This study uses a quantitative approach with a causal research type. The population in this study were 250 students of class VII MTs Negeri 2 Bandar Lampung in the 2024/2025 Academic Year. Through the Slovin Technique, a sample of 70 people was obtained. The data collection technique used questionnaires, interviews, and observations. So that the data to be obtained is quantitative data. Primary data is obtained directly from distributing questionnaires and interviews with respondents in the field. While secondary data is obtained from the results of observations, documentation, and theories from the literature, background documentation and school activities at MTs Negeri 2 Bandar Lampung. The results of this study indicate that there is a positive and significant influence in the implementation of the independent learning curriculum on learning outcomes in the Fiqh subject at MTs Negeri 2 Bandar Lampung, which can be seen in the calculation of the correlation coefficient and t-test. From the results of the correlation coefficient calculation, it can be said that the level of significance is 33.2%, or 0.332 and the rest is influenced by other factors. So from the positive rcount and the tcount of 2.903 compared to ttable 1.668, so that tcount ttable, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, which means that there is a significant positive influence.